Computational Model of Nano-Pharmacological Particles for the Clinical Management of Stenotic and Aneurysmatic Coronary Artery in the Human Body - Ibrahim Fetuga; Olabode Olakoyejo; Omotayo Oluwatusin; Adekunle Adelaja; Joshua Gbegudu; kolade Aderemi; Ebenezer Adeyemi (Nigerian Journal of Technological Development, 2023)
This work presents a three-dimensional computational study of nanoparticles (metallic and non-metallic) suspended in blood flowing through a diseased artery with both stenosis and aneurysm. From the perspective of pharmacodynamics and heat transfer, the influence of nanoparticles on hemodynamic indicators was investigated in a diseased artery. The blood was flowing fluid, steady-state, incompressible, homogeneous, and Newtonian, while the artery was a rigid wall. The three-dimensional continuity, Navier-Stokes, and energy equations were solved numerically by using a RAN-based standard k-ω model, which was performed on the ANSYS commercial software package. The influence of different selected nanoparticles (Al2O3, CuO, SiO2, and ZnO), nanoparticle concentration (1.0%-4.0%), and nanoparticle diameters (25 nm - 100 nm) on hemodynamic parameters such as velocity, temperature, turbulence intensity, more particularly skin friction coefficient and Nusselt number of the blood flow on the diseased artery, was also investigated. The streamlines, contours, and plots were adopted to better visualize the blood flow behavior in an artery with stenosis and aneurysm. The numerical results revealed that at a 4.0% nanoparticle concentration, CuO nanoparticles greatly reduced the blood velocity by 1.96% compared to other nanoparticles. About 0.66%-2.05% reduction in the blood velocity could be achieved by increasing the nanoparticle concentration from 1.0% to 4.0%. The SiO2 blood nanofluid showed the best result in augmentation of the Nusselt number by 53.0%. However, the nanoparticle diameter and concentration showed an insignificant effect on the skin friction factor